Bimetallic Catalysts: A Novel Approach to High‐Performance Aliovalent‐Substituted Catalysts—2D Bimetallic MOF‐Derived CeCuOx Microsheets (Small 42/2019). Issue 42 (15th October 2019) - Wang, Qingyue; Li, Zhimin; Bañares, Miguel A.; Weng, Lu‐Tao; Gu, Qinfen; Price, Jason; Han, Wei; Yeung, King Lun
Abstract : In article number1903525, Wei Han, King Lun Yeung, and co‐workers develop a synthesis approach to binary metal oxides by controlled thermal transformation of bimetallic metal–organic framework precursors. The approach is capable of manipulating the morphology and structure of binary metal oxides as high‐performance environmental catalysts for complete oxidation of volatile organic compounds under the conditions of low temperature and high humidity.